Creator of the present in an attempt to understand the future or what can be counted as, but not reduced to, Kissinger’s legacy - Šuvaković, Uroš V. (Napredak, 2024)
The text was written with an idea of reviewing the book The Age of A.I. and Our Human Future (2021/2022) by Henry Kissinger and his eminent associates Eric Schmidt and Daniel Huttenlocher, which was published in the USA when Kissinger was 99 years old. Since in the meantime this US statesman passed away at the age of 101, it was impossible not to take into consideration and, at least briefly, not point to Kissinger’s main accomplishments in international relations and diplomacy, his attitudes relevant for the Yugoslav crisis, and then look at this diplomat’s attempt in the book about artificial intelligence to perceive its potentials and, by understanding its advantages and shortcomings, to model the direction of the development of humanity. That is why this paper consists of two parts. The first part sketches Kissinger’s influence of US foreign affairs and making far-reaching foreign policy decisions of the USA, which created the world we used to know in the second half of the 20th century, with a particular emphasis on the establishment of relations between the People’s Republic of China and the USA, and the détente policy of the USA and the USSR. In the second part, attention is dedicated to Kissinger’s analyses and warnings about the emergence and development of artificial intelligence. Although he delved into this field at a rather advanced age, his insights are extremely important, particularly given his striving for international cooperation in the regulation of this matter.
Keywords: Henry Kissinger; diplomacy; artificial intelligence